Effect of Cutting Speed and Depth on the Course of Resultant Force Acting on a Cultivator Tine (Agricultural Engineering, 2016)
The paper presents research results on the effect of cutting depth and speed on the resultant force tilt angle and location of its application point on a flexible tine ended with a cultivator point. The studies were carried out in field conditions in sandy clay with the gravimetric moisture of 11.2% and volumetric density of 1470 kg·m−3. Tines whose flexibility coefficient was 0.0061; 0.0711; 0.0953 and 0.1406 m·kN−1 were used. It was found out that that the resultant force tilt angle raises at the increase of the cutting speed and drops at the increase of depth but this angle and its gradient at the increase of the cutting depth grow along with the decrease of the flexibility coefficient of tines. The increase of the cutting speed and depth causes the decrease of both the distance of the resultant force application point on the tool from the bottom of a furrow and a proportion of this parameter to the cutting depth. The courses of the distance of the resultant force application point on the tool from the bottom of a furrow and courses of proportion of this parameter to the cutting depth as the function of cutting do not differ significantly for tines with higher flexibility coefficients while for the most rigid tine values of these parameters and their gradients are higher. All obtained courses of the analysed values as a function of depth and cutting speed were described with regression equations.